2012
DOI: 10.2527/jas.2011-4334
|View full text |Cite
|
Sign up to set email alerts
|

Fiber fermentability effects on energy and macronutrient digestibility, fecal traits, postprandial metabolite responses, and colon histology of overweight cats

Abstract: Considering the different potential benefits of divergent fiber ingredients, the effect of 3 fiber sources on energy and macronutrient digestibility, fermentation product formation, postprandial metabolite responses, and colon histology of overweight cats (Felis catus) fed kibble diets was compared. Twenty-four healthy adult cats were assigned in a complete randomized block design to 2 groups of 12 animals, and 3 animals from each group were fed 1 of 4 of the following kibble diets: control (CO; 11.5% dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 40 publications
7
40
2
3
Order By: Relevance
“…More data are available on total tract crude protein digestibility; however, results are conflicting, with some researchers reporting decrease in apparent total tract N digestibility for beet pulp diets compared to a 0% supplemental fiber control diet or cellulose diets [9,11,14,18] and others reporting no differences [8,15,19,23]. Results are potentially due to differences among studies in fiber inclusion levels, interactions between dietary matrix and the fiber and the numbers of animals utilized.…”
Section: Traditional Fiber Sources Used In Companion Animal Nutritionmentioning
confidence: 99%
“…More data are available on total tract crude protein digestibility; however, results are conflicting, with some researchers reporting decrease in apparent total tract N digestibility for beet pulp diets compared to a 0% supplemental fiber control diet or cellulose diets [9,11,14,18] and others reporting no differences [8,15,19,23]. Results are potentially due to differences among studies in fiber inclusion levels, interactions between dietary matrix and the fiber and the numbers of animals utilized.…”
Section: Traditional Fiber Sources Used In Companion Animal Nutritionmentioning
confidence: 99%
“…43 A more recent study revealed that different fiber sources can induce different physiological responses in overweight cats, including the reduction of energy digestibility, greater inclination to favor glucose metabolism (with SCF), or gut health improvement (with beet pulp), according to their different solubilities and fermentation rates. 44 On the other hand, to serve as a sorbent material in the gut, smaller particles of dietary fiber may be more active than the coarse, because more smallsized particles than large-sized particles greatly increases the surface area in the same weight of fiber. Therefore, both fiber source and particle size may play an important role in fermentability and energy intake.…”
Section: Scf Significantly Enhanced Hepatic Fgf21 Signalingmentioning
confidence: 99%
“…These actions are most likely performed by insoluble and non‐fermentable fibres, such as sugar cane fibres. Sugar cane fibre is a source of insoluble fibre and has been used successfully in feline diets (Fischer et al., ), because their relatively low fermentability insoluble fibres allow for higher inclusion with less negative effects like gas formation and soft stools which are associated with soluble and fermentable fibres (Fischer et al., ).…”
Section: Introductionmentioning
confidence: 99%